Under the tiles - Tse, Aimee; Leech, Judy (Macmillan Education Australia South Yarra, Vic., 1997)
Under the Tiles by E.V. Thompson is a historical novel set in Cornwall, England, during the 19th century. The story follows the lives of a group of Cornish miners who discover a hidden fortune beneath the tiles of an old house. As they grapple with the moral and legal implications of their find, tensions rise within the community. The novel explores themes of greed, loyalty, and the complexities of human nature in the face of unexpected fortune, while also delving into the hardships of mining life and the class struggles of the time.